Modelling the Subjects of Skeletal and Muscular System: Mobile Applications - Cem Gerçek (Anı Publishing, 2019)
The existence of applications for such subjects as skeletal and muscular system in biology- where visual learning is important- is a necessity for teaching. This research basically aims to analyse applications for skeletal and muscular systems available in Apple, Google Play and Amazon virtual stores. This research employs document analysis- one of the qualitative research method. Applications available in virtual stores for skeletal and muscular system were reviewed in this research. The data collected were analysed through content analysis. Consequently, 35 applications in total were found for use with smart phones in relation to skeletal and muscular system. The results showed that the applications concerning skeletal and muscular system could be divided into 5 categories (Game, entertainment, animation, 2D and 3D visual based applications). Applications concerning skeletal and muscular system can be used in teaching so as to make diffarence for education and to increase permanence in learning.